Kebijakan Pengembangan Budidaya Tanaman Bambu untuk Pengelolaan Berkelanjutan DAS Aesesa Flores - Noywuli, Nicolaus; Sapei, Asep; H. Pandjaitan, Nora; Eriyatno, Eriyatno (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2019)
The existence of Aesesa Flores (AF) watershed is very important for people in Ngada and Nagekeo Regency of Flores island. The AF watershed provides water, land use, economic and other environmental services. However, the excessive exploitation is a major threat for the existence of the AF watershed. The degradation of the AF watershed function such as reduction in river debit, increase of critical land, land use change as well as the problem of poverty. The upstream area is intended as a conservation area where Watu Ata nature preservation park is located, the bamboo forest and Bajawa as the capital city of Ngada Regency. The downstream area is not only as capital city of Nageko Regency but also as paddy field area. One of the activity to improve the watershed function is through a comprehensive and sustainable management policy design based on characteristics and carrying capacity of the AF watershed. This research was conducted in April-May 2018 and the the purpose of the study is to analyzed key factors and establishing an alternative for sustainable management policy development of AF watershed using a prospective method. This study using mainly primary data obtained from the seven local experts through the filling of the questionnaire. The result shows that there are 22 attribute factors and it identified as 10 key factors. The main two key factors are bamboo cultivation, processing technology of bamboo, enlargement of bamboo cultivation area and practicing the soil and water conservation technique. The 10 key factors then become input for designing the management policy of AF watershed. Bamboo become the dominant and key factor because bamboo could be developed into biomass energy plant and it serves social, economic and ecological values for the local people of Ngada and Nagekeo Regency. Bamboo cultivation has a good prospect financially for the local people.